1996
DOI: 10.1002/(sici)1522-7154(1996)2:2<80::aid-anxi3>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Somatotype in panic patients

Abstract: The aim of the study was to test whether an association exists between asthenic somatotype, as measured by the Quetelet index, and panic and or agoraphobia. Ninety‐nine cases with panic and/or agoraphobia diagnosed at the psychiatric outpatient clinic of a general teaching hospital were compared to 99 controls with psychiatric conditions other than panic and agoraphobia, and to 64 medical controls, matched by age and gender. No differences in weight, height and raw Quetelet and ponderal indexes were found betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 21 publications
(27 reference statements)
0
2
0
Order By: Relevance
“…The Beighton system is based on measuring the degree of certain standardized movements of the joints, and its reliability has been proven in several previous studies [e.g., Beighton, 1988]. Both JHS and panic anxiety have been related to collagen-altering disorders such as mitral valve prolapse [MVP; Matuzas et al, 1989], Marfan's syndrome, Ehlers-Danlos syndrome, and the asthenic somatotype [Bulbena et al, 1996;Kellet et al, 1981], among others. Studies relating to MVP and anxiety have shown positive results indicating a higher prevalence of panic anxiety in patients with this condition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Beighton system is based on measuring the degree of certain standardized movements of the joints, and its reliability has been proven in several previous studies [e.g., Beighton, 1988]. Both JHS and panic anxiety have been related to collagen-altering disorders such as mitral valve prolapse [MVP; Matuzas et al, 1989], Marfan's syndrome, Ehlers-Danlos syndrome, and the asthenic somatotype [Bulbena et al, 1996;Kellet et al, 1981], among others. Studies relating to MVP and anxiety have shown positive results indicating a higher prevalence of panic anxiety in patients with this condition.…”
Section: Introductionmentioning
confidence: 99%
“…Studies relating to MVP and anxiety have shown positive results indicating a higher prevalence of panic anxiety in patients with this condition. Moreover, patients with panic have shown a significant association between MVP and asthenic somatotype, earlier onset of panic, and higher frequency of attacks [Bulbena et al, 1996;Matuzas et al, 1989]. Results indicating that panic anxiety is more prevalent in people with joint laxity and/or MVP have encouraged an interest in examining how these two conditions interact with common fears.…”
Section: Introductionmentioning
confidence: 99%